Comparative visual ecophysiology of mid-Atlantic temperate reef fishes - Andrij Z. Horodysky; Richard W. Brill; Kendyl C. Crawford; Elizabeth S. Seagroves; Andrea K. Johnson (Biology Open, 2013)
Summary The absolute light sensitivities, temporal properties, and spectral sensitivities of the visual systems of three mid-Atlantic temperate reef fishes (Atlantic spadefish [Ephippidae: Chaetodipterus faber], tautog [Labridae: Tautoga onitis], and black sea bass [Serranidae: Centropristis striata]) were studied via electroretinography (ERG). Pelagic Atlantic spadefish exhibited higher temporal resolution but a narrower dynamic range than the two more demersal foragers. The higher luminous sensitivities of tautog and black sea bass were similar to other benthic and demersal coastal mid-Atlantic fishes. Flicker fusion frequency experiments revealed significant interspecific differences at maximum intensities that correlated with lifestyle and habitat. Spectral responses of the three species spanned 400–610 nm, with high likelihood of cone dichromacy providing the basis for color and contrast discrimination. Significant day-night differences in spectral responses were evident in spadefish and black sea bass but not tautog, a labrid with characteristic structure-associated nocturnal torpor. Atlantic spadefish responded to a wider range of wavelengths than did deeper-dwelling tautog or black sea bass. Collectively, these results suggest that temperate reef-associated fishes are well-adapted to their gradient of brighter to dimmer photoclimates, representative of their unique ecologies and life histories. Continuing anthropogenic degradation of water quality in coastal environments, at a pace faster than the evolution of visual systems, may however impede visual foraging and reproductive signaling in temperate reef fishes.